Residual Catalatic Activity: a Rapid Screening Tool to Verify Cooking Temperature of Fish and Shellfish Meats - Musleh Uddin; Emiko Okazaki; Mita Wahyuni; Munehiko Tanaka (Jurnal Pengolahan Hasil Perikanan Indonesia, 2005)
Inadequate cooking and improper holding times of processed foods are common causes of food-borne disease outbreaks, therefore, proper cooking is necessary to keep them sate for consumers. Residual catalytic activity test was employed to verify cooking adequacy of fish and shellfish meats between 60 and 90 `C with 5, 15 and 30 min holding times. The catalytic activity defined as the decomposition of H2O2 into H202 and O2, The enzyme catalase retained its full activity up to 66 0C in both fish and shellfish meats. This sensitive test was able to detect cooking temperatures of fish and shellfish meats up to 74 and 72 oC respectively, which are the recommended safe temperatures (USDA-FSIS, 2001). The method provides a rapid and simple means for verifving adequacy of heat-processing of fish and shellfish meats.Key words:. catalatic activity, cooking adequacy. Fish. shellfish